Localities at the center : native place, space, and power in late imperial Beijing - Belsky, Richard (Richard David) (Harvard East Asian monographs, 2005)
"A visitor to Beijing in 1900, Chinese or foreign, would have been struck by the great number of native-place lodges serving the needs of scholars and officials from the provinces. What were these native-place lodges? How did they develop over time? How did they fit into and shape Beijing's urban ecology? How did they further native-place ties?" "In answering these questions, the author considers how native-place ties functioned as channels of communication between China's provinces and the political center; how sojourners to the capital used native-place ties to create solidarity within their communities of fellow provincials and within the class of scholar-officials as a whole; how the state co-opted these ties as a means of maintaining order within the city and controlling the imperial bureaucracy; how native-place ties transformed the urban landscape and social structure of the city; and how these functions were refashioned in the decades of political innovation that closed the Qing period." "Native-place lodges are often cited as an example of the particularistic ties that characterized traditional China and worked against the emergence of a modern state based on loyalty to the nation. The author argues that by fostering awareness of membership in an elite group, the native-place lodges generated a sense of belonging to a nation that furthered the reforms undertaken in the early twentieth century."--Jacket.